Preparation for bias, racial‐ethnic socialization competency, and Latinx adolescent mental health - Casandra J. Gomez Alvarado; Lisa Kiang; Riana E. Anderson; Howard C. Stevenson; N. Keita Christophe; Shawn C. T. Jones; Gabriela Livas (Journal of Research on Adolescence, 2026)
Abstract Although parental preparation for bias messages theoretically protect adolescents from the damaging impact of discrimination, they have been linked to mental health challenges in Latinx adolescents. Parental racial‐ethnic socialization (RES) competency has been proposed to potentially explain this discrepancy. The present study examined whether RES competency (confidence, skill, stress) moderated the relation between parental preparation for bias and adolescent mental health symptoms (internalizing and externalizing) in Latinx families. Latinx parents ( N = 210, M age = 42.63, SD = 8.68, 56% female) of adolescents ages 10 to 18 completed online surveys. The majority of parents were born in the United States (71%) and spoke English at home (76%). Main effects revealed that RES confidence was negatively associated with parent‐reported adolescent symptoms of psychopathology (internalizing: β = −.07, p < .05; externalizing: β = −.10, p < .01). As predicted, RES stress (general stress, call to action stress) moderated the relation between preparation for bias and parent‐reported adolescent internalizing (RES general stress: β = .09, p < .01; RES call to action stress: β = .11, p < .01) and externalizing symptoms (RES general stress: β = .08, p < .01; RES call to action stress: β = .09, p < .01). These findings underscore the importance of supporting parents with high stress around having RES conversations as well as leveraging existing Latinx parenting strengths (i.e., RES confidence) to support Latinx adolescent mental health.